2021
DOI: 10.1038/s41598-021-92120-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase (COX)-2 modulates Toxoplasma gondii infection, immune response and lipid droplets formation in human trophoblast cells and villous explants

Abstract: Congenital toxoplasmosis is represented by the transplacental passage of Toxoplasma gondii from the mother to the fetus. Our studies demonstrated that T. gondii developed mechanisms to evade of the host immune response, such as cyclooxygenase (COX)-2 and prostaglandin E2 (PGE2) induction, and these mediators can be produced/stored in lipid droplets (LDs). The aim of this study was to evaluate the role of COX-2 and LDs during T. gondii infection in human trophoblast cells and villous explants. Our data demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 100 publications
2
23
0
Order By: Relevance
“…It has been shown that inhibition of the host COX-2 enzyme resulted in the decrease of parasite burden in the brain and intraperitoneal macrophages of Calomys callosus rodents (8). Similar results were observed in human trophoblasts and villous explants treated with COX-2 inhibitors (9). Host lipoxygenases, appear to be involved in the production of anti-inflammatory responses.…”
Section: Introductionsupporting
confidence: 83%
“…It has been shown that inhibition of the host COX-2 enzyme resulted in the decrease of parasite burden in the brain and intraperitoneal macrophages of Calomys callosus rodents (8). Similar results were observed in human trophoblasts and villous explants treated with COX-2 inhibitors (9). Host lipoxygenases, appear to be involved in the production of anti-inflammatory responses.…”
Section: Introductionsupporting
confidence: 83%
“…Conversely, in granulosa cells of periovulatory follicles, PGE 2 upregulates PLIN2 [93]. And in human trophoblastic cells, COX2 inhibition reduces LD production induced by the intracellular parasite Toxoplasma gondii [94]. These limited studies suggest that PGs may have cell-type specific roles in regulating LD dynamics and lipid storage.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, here is the first study showing Giardia -induced COX-2/PGE2 enhancement in macrophages. However, some studies have indicated that COX-2/PGE2 can induce anti-inflammatory profiles in cells including macrophages or tissues infected by some intracellular protozoan parasites including Toxoplasma gondii , Trypanosoma cruzi , or Leishmania [ 42 46 ]. The difference might be due to different modes of parasitism (extracellular versus intracellular).…”
Section: Discussionmentioning
confidence: 99%